2020
DOI: 10.1111/ijpo.12698
|View full text |Cite
|
Sign up to set email alerts
|

Beyond sleep duration: Sleep timing as a risk factor for childhood obesity

Abstract: Background: Ample evidence attests to the relationship between short sleep duration, sleep problems and childhood obesity. However, few studies have examined the association between sleep timing and obesity in children. Objectives: To investigate how sleep duration, problems and timing relate to obesity and obesogenic behaviours in children. Methods: Eighty-five children (58.8% girls) with severe obesity and mean (SD) age of 12.1 (2.9) years, were matched by age and sex with peers with normal weight (n = 85,12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 53 publications
(210 reference statements)
1
48
0
Order By: Relevance
“…A small number of studies have reported that later bed and sleep onset times are independently associated with higher BMI z-score [7, 8], waist circumference and percent body fat [8], overweight and obesity [7, 9], and obesity severity in adolescents [10]. This is the first study to report sex-specific associations in a large and nationally representative sample of adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of studies have reported that later bed and sleep onset times are independently associated with higher BMI z-score [7, 8], waist circumference and percent body fat [8], overweight and obesity [7, 9], and obesity severity in adolescents [10]. This is the first study to report sex-specific associations in a large and nationally representative sample of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is a multidimensional construct of partly overlapping dimensions, and it is increasingly recognised that that parameters such as sleep timing and quality may be influential with regards to health [6]. A small number of studies have found that later bed and sleep onset times are associated with higher body mass index (BMI) z-score [7, 8], waist circumference and percent body fat [8], overweight and obesity [7, 9], and obesity severity in adolescents [10]. Sleep quality encompasses an array of continuity and architecture features [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is a multidimensional construct of partly overlapping dimensions, and it is increasingly recognised that parameters such as sleep timing and quality may also be influential with regards to health (Miller et al, 2015). A small number of studies have found that later bed and sleep onset times are associated with higher body mass index (BMI) z ‐score (Jarrin et al, 2013; Olds et al, 2011), waist circumference and percent body fat (%BF; Jarrin et al, 2013), overweight and obesity (Olds et al, 2011; Skjåkødegård et al, 2021), and obesity severity in adolescents (Hayes et al, 2018). Sleep quality encompasses an array of continuity and architecture features (Ohayon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Factors related to food intake, such as changes in meal distribution throughout the day (Garaulet et al, 2013;Mota et al, 2019) and/or type of food consumed (Silva et al, 2016;Cetiner et al, 2021), and physical activity pattern (Rutters et al, 2014;Alves et al, 2017) may also explain weight change due to circadian disturbances. Other studies have failed to find associations between SJL and anthropometric parameters (Rutters et al, 2014;Alves et al, 2017;Skjakodegard et al, 2021). However, social jetlag was found to be associated with percentage weight loss, body weight loss (kg) and BMI reduction in bariatric patients 6 months after surgery (Carvalho et al, 2021).…”
Section: Discussionmentioning
confidence: 94%